TANK-Binding Kinase 1-Dependent Responses in Health and Autoimmunity - Louis, Cynthia; Burns, Chris; Wicks, Ian (Frontiers in Immunology, 2018)
The pathogenesis of autoimmune diseases such as Rheumatoid Arthritis (RA) and Systemic Lupus Erythematosus (SLE) is driven by genetic predisposition and environmental triggers that lead to dysregulated immune responses. These include the generation of pathogenic autoantibodies and aberrant production of inflammatory cytokines. Current therapies for RA and other autoimmune diseases reduce inflammation by targeting inflammatory cytokines, most of which are innate response cytokines, resulting in generalized immunosuppression. Next generation therapies aim to treat disease while maintaining a functional immune system. Therapies that target the germinal centre (GC) reaction and/or antibody secreting plasma cells (PC) potentially provide a novel approach. TANK-binding kinase 1 (TBK1) is an IKK-related Serine/Threonine kinase best characterized for its involvement in innate antiviral responses through the induction of type I interferons. TBK1 is also gaining attention for its roles in humoral immune responses. In this review, we discuss the role of TBK1 in distinct pathways involved in the development and maintenance of antibody responses, with particular emphasis on its potential relevance in the pathogenesis of humoral autoimmunity. First, we review the role of TBK1 in the induction of type I IFNs. Second, we highlight TBK1 in ICOS signaling to the GC T follicular B helper (TFH) population. Third, we discuss emerging evidence of TBK1 in autophagic pathways and potential implications for immune cell function. Finally, we discuss the therapeutic potential of TBK1 inhibition in autoimmunity.